BENTUK PENYAJIAN TARI RADDAT ANAK DUYONG DI DESA BEKUT KECAMATAN TEBAS KABUPATEN SAMBAS - Nurfitri, Annisa; Syahrani, ,Agus; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research was to know the basic and the supportelements which could be found in Raddat Anak Duyong dance. The result of this research was the description of the main element and support element of Raddat Anak Duyong dance. There are four kind of movements, which is divided as the first movement, the center movement (substance) and the closing movement. The floor design that used has vertical, horizontal, square and V line pattern.The low design, asyimmetric, angular, flat, pure, deep, symmetrical, and static was the top design used. Raddat Anak Duyong dance told about the people in the old period which is not believe in God.The dramatic design shape was doubled cone with the dynamic which exist in this dance have not any variation, the dancer movement adjusting to the music tempo and group composition used cohesive design and by turns. The music used Tar as music instrument and Syair Dialek Melayu Sambas song. The make up and the custom used was malay teluk belangak custom, baju kurung with Sambas original materialÂ  and natural make up. The show place used can be at proscenium and arena stage. The result of this research can be used to be a teaching material in art and culture on 8th grader.Keywords : Form of presentation, Raddat Anak Duyong Traditional Dance, Melayu Sambas.Â